Stenting of the right ventricular outflow tract. Issue 21 (11th July 2013) - Stumper, Oliver; Ramchandani, Bharat; Noonan, Patrick; Mehta, Chetan; Bhole, Vinay; Reinhardt, Zdenka; Dhillon, Rami; Miller, Paul A; de Giovanni, Joseph V
Abstract : Objective: To assess the indication, technical aspects, and outcome of stenting of the right ventricular outflow tract (RVOT) in the management of symptomatic patients with severely limited pulmonary blood flow. Methods: Retrospective case note and procedure review of patients undergoing stenting of the RVOT over an 8 year period. Patients: Between 2005 and 2012, 52 selected patients underwent percutaneous stent implantation into a very narrow RVOT to improve pulmonary blood flow. Median age at stent implantation was 63 (range 4–406) days and median weight was 3.8 (1.7–12.2) kg. Results: 52 patients underwent stent implantation. Median procedure time was 57 (24–260) min and fluoroscopy time 16 (5.5–73) min. There was one procedural death (1.9%) and one emergency surgery (1.9%). Saturations increased from 71% (52–83%) to 92% (81–100%) (p<0.001). Two patients required early shunts due to inadequate palliation and two died from non-cardiac causes. Sixteen further catheter interventions were undertaken (balloon in 7, further stent in 9). Twenty-nine patients underwent delayed surgery (complete repair in 26, palliative in 3) at a median of 172 (52–758) days post-stenting. Left pulmonary artery Z score increased from a pre-interventional value of −1.75 (−4.96 to 0.67) to a pre-surgical value of −0.55 (−4.12 to 1.97), (p<0.01). Median right pulmonary artery Z score increased from −2.63 (−7.70 to 0.89) to −0.75 (−6.69 to 1.18) (p<0.01) . Seventeen patients remain well palliated after a median of 122 (40–286) days. Conclusions: Stenting of the RVOT is an effective treatment option in the initial management of selected patients with very reduced pulmonary blood flow.